Financial stress and oil market volatility: new evidence. Issue 1 (2nd January 2023) - Pang, Dan; Ma, Feng; Wahab, M. I. M.; Zhu, Bo
ABSTRACT: This study investigates the effect of financial stress (financial stress index; FSI) on oil market realized volatility using Markov-regime switching MIDAS models. The empirical results show that FSI can remarkably improve the forecast accuracy of the oil market. Moreover, FSI measured by the United States can obtain more useful information than that measured by the world. Our findings are robust and reliable via alternative evaluation methods from both statistical and economic aspects.